Instability in a marginal coral reef: the shift from natural variability to a human‐dominated seascape. Issue 3 (22nd July 2010) - Lybolt, Matt; Neil, David; Zhao, Jianxin; Feng, Yuexing; Yu, Ke-Fu; Pandolfi, John
Abstract : As global climate change drives the demise of tropical reef ecosystems, attention is turning to the suitability of refuge habitat. For the Great Barrier Reef, are there historically stable southern refugia where corals from the north might migrate as climate changes? To address this question, we present a precise chronology of marginal coral reef development from Moreton Bay, southeast Queensland, Australia. Our chronology shows that reef growth was episodic, responding to natural environmental variation throughout the Holocene, and that Moreton Bay was inhospitable to corals for about half of the past 7000 years. The only significant change in coral species composition occurred between 200 and 50 years ago, following anthropogenic alterations of the bay and its catchments. Natural historical instability of reefs, coupled with environmental degradation since European colonization, suggests that Moreton Bay offers limited potential as refuge habitat for reef species on human time scales.